Forensically important flesh fly species in Thailand: Morphology and developmental rate - Sukontason K. (2014)
Forensically important flesh fly species in Thailand have been investigated for their larval morphology and developmental rate to increase the forensic entomology database in Thailand and nearby countries. Sarcophaga (Liosarcophaga) dux Thomson, Sarcophaga (Liopygia) ruficornis (Fabricius), and Sarcophaga (Boettcherisca) peregrina (Robineau-Desvoidy) are the species of greatest forensic importance. The third instars of these species are similar in morphological appearance, making it difficult or impossible to differentiate between them based on external morphological characteristics. This study compares these important characteristics and reveals that the most distinctive is the posterior spiracle, followed by the number of papillae on the anterior spiracle. For confirmation of these species, the unique characteristics of adult males are also shown for accurate identification. Both the third instar and adult male characteristics are keys to identifying these species. In addition, the developmental rate of S. dux was examined in northern Thailand during 2002-2003 under natural ambient temperature (≈24-28°C) and a natural light/dark photoperiod (≈12:12 h), indicating relatively rapid larval development in summer (March-June), pre-pupae (stop moving) initiated at 72 h. In the rainy season (July-October), pre-pupae initiated at 72 or 96 h, whereas pre-pupae initiated at 96 h in winter. © Springer-Verlag 2010.